Genocias ir rezistencija Nr. 6(2) - Jonušauskas, Laurynas; Maslauskienė, Nijolė; Bubnys, Arūnas; Streikus, Arūnas; Kuprytė, Jurgita; Račkauskaitė, Živilė; Müller-Enbergs, Helmut; Rupšienė, Alisa (Genocidas ir rezistencija, 1999)
Pilnas leidinys (nuskenuota popierinė versija)